Principi del «flipped learning» per lo sviluppo dell’interazione orale a livello B1 in italiano come lingua straniera - Mertelj, Darja (Studia Romanica Posnaniensia, 2020)
The paper first brings an overview of spoken interaction in FL and flipped learning principles. This overview is followed by a thorough didactic report on how these two processes can be merged, how teaching materials can be prepared, and how the teaching and learning process can be systematically developed in order to extensively support learners’ efforts to speak at level B1 in Italian as a FL. Both positive and less positive aspects of a one-semester project are discussed. Finally, some conclusive glotodidactic implications stemming from the experience are proposed.